Interfacial adhesion and deformation of thermotropic liquid crystal polymers in engineering thermoplastics: Blends of a poly(ester amide) with nylon 6 and a polyester with PBT - Seo, Y (JOHN WILEY & SONS INC, 1997)
A new method was sought to produce in situ composites by the addition of a third component that would react with matrix polymers and thermotropic liquid crystal polymers to form graft copolymers, which act as a compatibilizer at the interface. Morphological observation reveals the significance of compatibilization in immiscible polymer blends. Good adhesion at the interface by the produced compatibilizer enabled the finely dispersed liquid crystal phase to be deformed in shear flow without elongation, even when the viscosity of the matrix polymer was lower than that of the liquid crystal polymer. This study provides a way to produce a strong and tough in situ composite. (C) 1997 John Wiley & Sons, Inc.
Keywords: SITU COMPOSITE SYSTEM; MECHANICAL-PROPERTIES; POLY(ETHER IMIDE); POLYPROPYLENE; MORPHOLOGY; FLOW